(untitled) (Mongolian Journal of Agricultural Sciences, 2018)
A total 22 (30.5%) camels were infected with 34 echinococcal cysts out of 72 slaughtered camels in Khurmen soum of Southgobi province. The prevalence of infection in camels between 5-7 years (14/22) was 18.2-22.7% and 8 years camels (6/22) were 27.3%. The fertile cyst rate was 40.9% and sterile cyst rate was 22.7%. Camel cystic echinococcosis cyst status was fertile, sterile, abscessed and calcified. Most of the cysts were located in the lungs 54.5%, liver 27.3% and lung-liver 18.2% and were spherical in shape, unilocular and 1-3 cysts located in lung and liver of one camel, cyst diameter was 2-10 cm and with cyst fluid ranging from 1 to 200 ml. Camel echinococcal cysts status and appearance were revealed as age dependent, as older camels echinococcal cysts were revealed as calcified statistically significant (p=0.0458). Histologically, leucocyte infiltration and mild hepatocellular degeneration and infiltration in the liver were noticed. In lungs, there was proliferation of fibrous connective tissue and infiltration of mononuclear cells.